Moderate stability of risk and ambiguity attitudes across quantitative and qualitative decisions - Ohad Dan; Chelsea Y. Xu; Ruonan Jia; Emily K. Wertheimer; Megha Chawla; Galit Fuhrmann Alpert; Terri Fried; Ifat Levy (Scientific Reports)
Abstract Uncertainty lies at the heart of everyday choices, affecting both decisions about precise quantities and those with less tangible, more qualitative, outcomes. Previous literature on decisions under uncertainty focused on alternatives with quantifiable outcomes, for example monetary lotteries. In such scenarios, decision-makers make decisions based on success chance, outcome magnitude, and individual preferences for uncertainty. It is not clear, however, how individuals construct subjective values when outcomes are not directly quantifiable. To explore how decision-makers choose between non-quantifiable uncertain outcomes, we focus here on medical decisions with qualitative outcomes. Specifically, we ask whether decision-makers exhibit similar attitudes towards uncertainty, focusing on ambiguity, across domains with quantitative and qualitative outcomes. We designed an online decision-making task where participants made binary choices between alternatives offering either guaranteed low outcomes or potentially better outcomes that were associated with some uncertainty. Outcomes were either hypothetical monetary gains of varying magnitudes or levels of improvement in a hypothetical medical condition. We recruited 429 online participants and repeated the survey in two waves, which allowed us to compare the between-domain attitude consistency with within-domain consistency over time. We found that uncertainty attitudes were moderately correlated across domains and time. We discuss the implications and applicability of our paradigm to broader contexts with non-quantifiable outcomes.